Application of the Altman's Z-Score Method to Predict the Bankruptcy Potential of Indexed Bank Issuers in SRI-KEHATI (2015–2024) - Ika Puspita Sari; Andini Nurwulandari; Hasanudin Hasanudin (International Forum of Researchers and Lecturers, 2025)
Research on national banking using the Altman’s Z-Score analysis technique has been relatively extensive, but studies focusing specifically on banks indexed to SRI-KEHATI remain limited. The SRI-KEHATI Index is known as a benchmark for companies with strong sustainability, social responsibility, and good governance practices. This study aims to analyze the health trends of banks listed in the SRI-KEHATI Index during the 2015–2024 period by applying the second modified Altman’s Z-Score model (1993), which is widely recognized as a reliable indicator for assessing a company’s financial stability and risk of bankruptcy. The findings indicate that the overall Altman’s Z-Score trend of major banks within the SRI-KEHATI Index shows stability and a consistently healthy financial condition throughout 2015–2023. However, in 2024 there is a notable decline that requires further examination to determine whether it is caused by market fluctuations, structural challenges, or accounting adjustments. Despite this decrease, the overall financial health of the banks remains categorized as very good according to Altman’s model. The average Z-Score for all four banks analyzed is 6.457, which is well above the threshold of 2.6, indicating no significant bankruptcy risk. When evaluated individually, BMRI stands out as the healthiest with a Z-Score of 13.879, followed by BBNI with 5.971, BBRI with 3.175, and BBCA with 2.801. These results confirm that all four banks remain in a safe financial zone during the 2015–2024 period. Furthermore, the study’s four hypotheses are proven, reinforcing the argument that SRI-KEHATI indexed banks maintain strong financial resilience even amid post-Covid-19 challenges.